Cervical branch of the facial nerve approach for retrograde parotidectomy compared with anterograde parotidectomy. (November 2014) - Furusaka, Tohru; Tanaka, Akane; Matsuda, Hiroshi; Hasegawa, Hisashi; Asakawa, Takeshi; Shigihara, Shuntaro
Abstract Conclusion: The cervical branch of the facial nerve approach for parotidectomy is an excellent surgical technique that can reduce the incidence of facial nerve paralysis, surgical time, and surgical blood loss. Objective: To develop and evaluate a surgical technique for parotidectomy that can reduce the incidence of facial nerve paralysis. Methods: Retrograde parotidectomy following identification of the cervical branch of the facial nerve in 90 subjects was compared with standard anterograde parotidectomy in 100 subjects. Results: Retrograde parotidectomy with a cervical branch approach was associated with significant decreases in the incidence of facial nerve paralysis, surgical time, and surgical blood loss, compared with anterograde parotidectomy.